Goal-setting participation as strategic measurement performance for enhancing managerial performance through procedural fairness and interpersonal trust - Soni Agus Irwandi; Taufik Akbar (Universitas Hayam Wuruk Perbanas, 2014)
This research is a study of the behavior of the performance measurement strategy. Behavior is related to the participation of managers in setting performance goals that are measured in terms of financial and on-financial, that can affect managerial performance, with an intervening variable procedural fairness and interpersonal trust. The object of research was carried out at the level of middle and lower level managers in all companies in the Province of Banten and West Java are registered in the Indonesia Stock Exchange (IDX), with a sample of 205 managers. Results of the study showed that the manager's participation in setting performance goals that are measured in terms of financial and non-financial positively affect performance and managerial and procedural fairness. Beside, interpersonal trust partially mediates the effect of goal-setting participation managers on managerial performance.